2016
DOI: 10.1002/cssc.201501273
|View full text |Cite
|
Sign up to set email alerts
|

Cuprous Oxide as a Potential Low‐Cost Hole‐Transport Material for Stable Perovskite Solar Cells

Abstract: Inorganic hole‐transport materials are commercially desired to decrease the fabrication cost of perovskite solar cells. Here, Cu2O is introduced as a potential hole‐transport material for stable, low‐cost devices. Considering that Cu2O formation is highly sensitive to the underlying mixture of perovskite precursors and their solvents, we proposed and engineered a technique for reactive magnetron sputtering. The rotational angular deposition of Cu2O yields high surface coverage of the perovskite layer for high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
85
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(86 citation statements)
references
References 50 publications
0
85
0
Order By: Relevance
“…The PL spectra are usually used to explore the trap states and recombination properties of light-excited charge in semiconductors [23, 4042]. Figure 9 shows the PL spectra of CH 3 NH 3 PbI 3− x Cl x films deposited on bare TiO 2 and modified TiO 2 by CH 3 NH 3 I solutions with different concentrations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PL spectra are usually used to explore the trap states and recombination properties of light-excited charge in semiconductors [23, 4042]. Figure 9 shows the PL spectra of CH 3 NH 3 PbI 3− x Cl x films deposited on bare TiO 2 and modified TiO 2 by CH 3 NH 3 I solutions with different concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…The CH 3 NH 3 PbI 3− x Cl x film deposited on bare TiO 2 exhibits the highest intensity in PL spectra, corresponding to a higher charge recombination [23]. The CH 3 NH 3 PbI 3− x Cl x film deposited on modified TiO 2 by CH 3 NH 3 I with the concentration of 10 mg/ml shows the lowest peak intensity, indicating the lowest recombination rate [42] and thus the best photovoltaic performance. This is consistent with the results obtained in EIS characterization (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[9] This has pushed modern research to promote efficacious and low-cost inorganic HTLs such as Cu 2 O. Hossain et al [10] described the primary functiono fP SCs with differentH TM layers such as spiro-MeOTAD, NiO, CuI, CuSCN, and Cu 2 Ob yu sing simulation software. To overcome this issue, Nejand et al [12] reported Organic-inorganic halide perovskite solar cells (PSCs) have reachedc ertified efficiencies of over 23 %w ithe xpensive organic hole-transporting materials. Consequently,t his gives ar eason for the vital research relatedt oi norganic HTMs, especially Cu 2 O, in PSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Although a high PCE was obtained, the process relies on an organic PEDOT:PSS buffer layer between the CuO layer and the ITO substrate. Nejand 18 and Yu…”
Section: 13mentioning
confidence: 99%